Multidetector CT findings of primary pleural angiosarcoma : a systematic review, an additional cases report - Bo Mi Gil; Myung Hee Chung; Ki-Nam Lee; Jung Im Jung; Won Jong Yoo; Soon Seog Kwon; Heejeong Lee (Cancer Imaging, 2022)
Abstract Background To demonstrate and analyze the relatively common imaging findings in this rare primary pleural angiosarcoma (PPA). Case presentation Three cases of PPA, proven by video-assisted thoracic surgery biopsies are retrospectively reviewed. Patients were all male. Age ranges from 65 to 75 years old age (mean; 69). Major chief complaints were dyspnea and chest pain. One has a history of colon cancer, the other has a tuberculosis history and the other has no known history. Multidetector chest CT and PET CT were all done. Immunohistochemical studies were performed including CD31, CD34, or factor VIII-related antigen, vimentin, and cytokeratin. We also review the literatures on recently published PPA. All masses were from 1 to 10 cm. All three patients had multiple pleural based masses, which were ovoid in shape with relatively sharp margin in unilateral hemithorax. Multiple small circumscribed pleural masses are limited in the pleural space in two patients, whereas two, huge lobulated masses about up to 10 cm were present with pleural and extrapleural involvement in one patient. In two patients with pleural mass only, multiple pleural masses were only seen in parietal pleura in one patient and were in both visceral and parietal pleura in one patient. Pleural effusion were found in one side in one patient and in both sides in one patient. One angiosarcoma was arised from chronic tuberculotic pleurisy sequelae. All pleural masses are heterogenous with irregular internal low densities in all patients. Hematogenous metastases were found in liver, vertebra, rib in one patient, and were in lungs with mediastinal lymph node metastases in the other patient. Three patients survived for longer than 3months after diagnosis, but continued to deteriorate rapidly. Two patients underwent chemotherapy after surgical excision, and the other one with multiple metastases treated chemotherapy after CT-guided biopsy, but eventually all died. As a result of comparative analysis of a total of 13 patients’ images including 10 cases previously published, there was pleural effusion in all except 2 cases. Conclusions PPA were all necrotic without any vascularized enhancing nature, and manifested as unilateral circumscribed or localized pleural-based masses.